Narrative networks storied approaches in a digital age - Alleyne, Brian (Sage, 2015)
This book responds to the dynamic production and consumption of stories of all kinds in popular and academic cultures. It offers a comprehensive discussion of the underlying philosophical and methodological issues of narrative and personal narrative research as well as applying these to the current digital landscape. The book provides practical guidance on data management and use of software for the narrative researcher. Illustrated with examples from a range of fields and disciplines as well as the author's own work on hacking cultures and cultural activism, this title is a must for anyone wanting to learn about narrative approaches in social research and how to conduct successful narrative research in a digital age.